PENGARUH KUALITAS PELAYANAN TERHADAP KEPUTUSAN BERKUNJUNG KEMBALI (REVISIT INTENTION) WISATAWAN KE PESONA ALAM PUNCAK - Edwin Baharta (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This study aims to analyze the quality of service, and the decision of returning tourists to Pesona Alam Puncak, as well as further analyzing the quality of service to the intention of revisiting tourists to Pesona Alam Puncak. This study uses a cross-sectional method with a type of causal research. The research variables include information about quality, consulting, order taking, hospitality, storage, exclusion, billing, and payment. While the agreed variables are the intention to revisit who has a three-dimensional visit, plan to visit, and want to visit. Obtaining primary and secondary data with data collection techniques through field observations, questionnaires, and literature studies. The population determined is tourists visiting Pesona Alam Puncak in 2017 with a sample of 400 tourists. The results showed the quality of the service of Enchantment of Nature Pucak, specifically the management ability and employees received good responses from tourists. In addition, there are 208 tourists or 52% of tourists have made a return visit to Pesona Alam Puncak. Enchantment of Alam Puncak has extraordinary quality. Recommendation: Improving the quality of service in the form of employee competence Pesona Alam Puncak